Childhood maltreatment and DNA methylation: A systematic review - Cecil, Charlotte A.M.; Zhang, Yuning; Nolte, Tobias (Neuroscience and biobehavioral reviews, 2020)
•We review human studies on childhood maltreatment and DNA methylation.•The 72 studies identified were mainly retrospective and candidate-gene focussed.•While studies generally support a relationship, evidence to date is inconsistent.•Limitations include a lack of longitudinal data, low replication and confounding.•We provide 12 concrete recommendations for moving the field forward. DNA methylation (DNAm) – an epigenetic process that regulates gene expression – may represent a mechanism for the biological embedding of early traumatic experiences, including childhood maltreatment. Here, we conducted the first systematic review of human studies linking childhood maltreatment to DNAm. In total, 72 studies were included in the review (2008–2018). The majority of extant studies (i) were based on retrospective data in adults, (ii) employed a candidate gene approach (iii) focused on global maltreatment, (iv) were based on easily accessible peripheral tissues, typically blood; and (v) were cross-sectional. Two-thirds of studies (n = 48) also examined maltreatment-related outcomes, such as stress reactivity and psychiatric symptoms. While findings generally support an association between childhood maltreatment and altered patterns of DNAm, factors such as the lack of longitudinal data, low comparability across studies as well as potential genetic and ‘pre-exposure’ environmental confounding currently limit the conclusions that can be drawn. Key challenges are discussed and concrete recommendations for future research are provided to move the field forward.